Evaluation of marketing authorization and clinical implementation of ulipristal acetate for uterine fibroids. Issue 5 (10th February 2022) - Middelkoop, Mei-An; de Lange, Maria E; Clark, T Justin; Mol, Ben Willem J; Bet, Pierre M; Huirne, Judith A F; Hehenkamp, Wouter J K
ABSTRACT: Ulipristal acetate (UPA) is a medical treatment for uterine fibroids and was authorized for surgical pre-treatment in 2012 after the conduct of the PEARL I and II randomized controlled trials and for intermittent treatment after the observational PEARL III and IV trials. However, UPA came into disrepute due to its temporary suspension in 2017 and 2020 because of an apparent association with liver injury. This clinical opinion paper aims to review the process of marketing authorization and implementation of UPA, in order to provide all involved stakeholders with recommendations for the introduction of future drugs. Before marketing authorization, the European Medicines Agency (EMA) states that Phase III registration trials should evaluate relevant outcomes in a representative population, while comparing to gold-standard treatment. This review shows that the representativeness of the study populations in all PEARL trials was limited, surgical outcomes were not evaluated and intermittent treatment was assessed without comparative groups. Implementation into clinical practice was extensive, with 900 000 prescribed treatment cycles in 5 years in Europe and Canada combined. Extremely high costs are involved in developing and evaluating pre-marketing studies in new drugs, influencing trial design and relevance of chosen outcomes, thereby impeding clinical applicability. It is vitally important that the marketing implementation after authorization is regulated in such way that necessary evidence is generated before widespread prescription of a new drug. All stakeholders, from pharmaceutical companies to authorizing bodies, governmental funding bodies and medical professionals should be aware of their role and take responsibility for their part in this process.